Residential Broadband, Second Edition - Abe, George (Cisco Press, 1999)
A comprehensive introduction to high-speed residential networks, integrating technical, business, and regulartory challenges. Surveys the various types of access networks: Cable TV, xDSL, FTTx, and wireless Defines basic technology requirements for implementing residential broadband and assessing the state of readiness Reviews the business conditions and regulatory practices that affect rollout and viability of residential networks Discusses the technologies and challenges associated with the in-home network Describes the new and existing entertainment and data services, and how to evaluate the demand for them Provides systems issues to be resolved in connecting access networks to home networks Residential Broadband, Second Edition aims to provide a comprehensive, accessible introduction to the topics surrounding high-speed networks to the home. It is written for anyone seeking a broad-based familiarity with the issues of residential broadband (RBB) including product developers, engineers, network designers, business people, professionals in legal and regulatory positions, and industry analysts. Readers will learn about the services that are driving the market, the technical issues shaping the evolution, and the network within the home and how it connects to the access network. The author explains the technical concerns, accessibility, the current state, and potential future of cable TV, xDSL, FTTx, wireless access networks, and home networks.